Dysgonic fermenter 3 bacteremia in a neutropenic patient with acute lymphocytic leukemia. - Aronson, N E (1988)
Persistent dysgonic fermenter 3 bacteremia occurred in a granulocytopenic leukemic patient on broad-spectrum antibiotic therapy. This is the first reported case of bacteremia with this fastidious gram-negative rod. Characteristic microbiology and antibiotic susceptibility testing are reviewed. Trimethoprim-sulfamethoxazole therapy eliminated the bacteremia.